Early Christian epigraphy, evil, and the apotropaic function of Romans 8.31 - Strawbridge, J (Brill Academic Publishers, 2017)
Epigraphic evidence offers an important and yet oft-neglected dimension to the history of biblical reception. One of the most curious cases of epigraphic incidence of a biblical text is the use of Romans 8.31. Within early Christian writings, this Pauline passage is used approximately 20 times across nine different writers before 604 CE. However, the words of Romans 8.31 may be found on at least 23 epigraphic artifacts from this same period, and in particular, on the door lintels of homes. This article explores what might account for the discrepancy between the literary and epigraphic use of Romans 8.31, the possible apotropaic function of this phrase, and how such evidence might inform the interpretation and reception of this Pauline passage.